2009
DOI: 10.1002/cjg2.1435
|View full text |Cite
|
Sign up to set email alerts
|

Seismological Evidences of the Crustal Structures and Tectonics in the Yinchuan Downfaulted Basin

Abstract: A high resolution deep seismic reflection profile of 68.9 km long across the Yinchuan faulted basin has been accomplished which for the first time yields the fine crustal structures, characteristics of deep fault system (Yellow River fault, Yinchuan fault and Eastern piedmont fault of Helanshan) of faulted basin in graben style, and the relationship between shallow and deep structures in Yinchuan basin. The results show that the upper crust is the region above a reflector with 8 s two‐way traveling time (about… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
24
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(28 citation statements)
references
References 2 publications
4
24
0
Order By: Relevance
“…Previous studies have identified two other inferred faults in the graben: the Luhuatai and Yinchuan-Pingluo faults, identified using seismic reflection data (Fig. 1b and c;Cai et al, 2006;Wang et al, 2007;Fang et al, 2009;Feng et al, 2011;Yang et al, 2009). However, the topographical analysis and field investigations of the present study show no conspicuous topographical or geologic evidence for tectonic deformation features on the alluvial surfaces, including the terrace risers and alluvial fans, which formed during the Holocene along the Luhuatai and Yinchuan-Pingluo faults (Fig.…”
Section: Identification Of Active Faultsmentioning
confidence: 92%
See 2 more Smart Citations
“…Previous studies have identified two other inferred faults in the graben: the Luhuatai and Yinchuan-Pingluo faults, identified using seismic reflection data (Fig. 1b and c;Cai et al, 2006;Wang et al, 2007;Fang et al, 2009;Feng et al, 2011;Yang et al, 2009). However, the topographical analysis and field investigations of the present study show no conspicuous topographical or geologic evidence for tectonic deformation features on the alluvial surfaces, including the terrace risers and alluvial fans, which formed during the Holocene along the Luhuatai and Yinchuan-Pingluo faults (Fig.…”
Section: Identification Of Active Faultsmentioning
confidence: 92%
“…Seismic reflection data show that the HHFZ, which runs along the eastern margin of the Helan Mountains, is the main fault forming the western boundary of the graben (Fig. 1b and c;Fang et al, 2009;Feng et al, 2011). The Huanghe Fault (HHF), along which the Yellow River flows to the NNE, is inferred to be a blind fault and its recent activity is unclear (Deng and Liao, 1996).…”
Section: Tectonic Settingmentioning
confidence: 93%
See 1 more Smart Citation
“…Earthquake activity is strong in this region; the Pingluo M 8 earthquake occurred in 1739, but its seismogenic structure has been controversial. Mao and Yao (1982), Li and Wan (1984) and Wu et al (2015), and many other scholars think that the earthquake seismogenic structure is the Yinchuan blind fault, but others believe the active Helandonglu fault is the seismogenic structure (Fang et al 2009;Lei et al 2015;Wang et al 2015). The current understanding of the blocks is obscure or ambiguous, which makes it difficult to analyze the mutual block movement and deformation in-depth.…”
Section: Geological Settingmentioning
confidence: 99%
“…Chai et al (2006) gave the blind fault activity characteristics in Yinchuan and the surrounding area comprehensively. Fang et al (2009) studied the relationship between the Huanghe, Yinchuan, and Helanshandonglu faults and their shallow and deep structure using a deep seismic reflection method. Other researchers (Zheng 2011;Yin et al 2013) then obtained the electrical structure of the Ordos block and JiangyuanNingxia region.…”
Section: Introductionmentioning
confidence: 99%